If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1y = 2y + -1 Reorder the terms: 8 + -1y = -1 + 2y Solving 8 + -1y = -1 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 8 + -1y + -2y = -1 + 2y + -2y Combine like terms: -1y + -2y = -3y 8 + -3y = -1 + 2y + -2y Combine like terms: 2y + -2y = 0 8 + -3y = -1 + 0 8 + -3y = -1 Add '-8' to each side of the equation. 8 + -8 + -3y = -1 + -8 Combine like terms: 8 + -8 = 0 0 + -3y = -1 + -8 -3y = -1 + -8 Combine like terms: -1 + -8 = -9 -3y = -9 Divide each side by '-3'. y = 3 Simplifying y = 3
| 9x+3=-32 | | 7x-2x=5x | | 3y^2=8y+3 | | 9-2(b+3)=4b | | r*r-10r+25=0 | | x+(x+5)=45 | | 5w^2+6=-17w | | -5-6p=2p+2 | | -7n+6=3(3n+10) | | 12.75x-15.35=3.124(2x+3) | | 2(5a-1)-4(-2a+3)= | | 21+9j+-10=-277 | | 1-6x=7+3x-8x | | y-(-75)=60 | | 13x-15=3(2x+3) | | 2x^3-12x^2-3x+192=0 | | 12x-15=3(2x+4) | | 8c=54 | | 7n+2n=81 | | 27x-1=19x+14+5x | | 4c-5+14c= | | 13=4x+-11 | | x/3=-19 | | 2(x+8)-4=2(x-7)+8 | | x-5[2x-3(x+6)]=-4(x-5) | | -11.3x=101.7 | | 3y+6=y^2 | | =6t | | 2.5-4f=10-2.5f | | (X+10)=(2x+5) | | =10y-15y | | -10=(a-1)+(a-3) |